RETRACTED: Extensive teaching of physics for students of technical specialties with the help of experimental units and computer simulation software - Semenov Alexander; Bebikhov Yuriy; Tatarinov Pavel; Zakharov Pavel; Korznikova Elena (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001